2018
DOI: 10.1002/uog.19091
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Italian Sonography for occiput POSition Trial Ante vacuum (R.I.S.POS.T.A.)

Abstract: Our prematurely discontinued randomized controlled trial did not demonstrate any benefit in terms of reduced risk of failed instrumental delivery or maternal and fetal morbidity in women undergoing sonographic assessment of fetal head position prior to vacuum extraction. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…We thank Drs Dall'Asta, Rizzo and Ghi for their comments 1 on our recently published randomized controlled trial evaluating the impact of intrapartum ultrasound prior to instrumental vaginal delivery on maternal and neonatal outcomes. 2 Several studies have indeed reported that ultrasound provides an improved diagnosis of fetal head position in labor, compared with digital vaginal examination, 3,4 but this was not a pre-established objective or outcome of our trial. Ultrasound is routinely used in our center to access occiput position when there is uncertainty following clinical examination, and this was a major detractor to recruitment of women for the trial, as several staff members felt that there was insufficient equipoise in these cases.…”
Section: Sirmentioning
confidence: 85%
See 1 more Smart Citation
“…We thank Drs Dall'Asta, Rizzo and Ghi for their comments 1 on our recently published randomized controlled trial evaluating the impact of intrapartum ultrasound prior to instrumental vaginal delivery on maternal and neonatal outcomes. 2 Several studies have indeed reported that ultrasound provides an improved diagnosis of fetal head position in labor, compared with digital vaginal examination, 3,4 but this was not a pre-established objective or outcome of our trial. Ultrasound is routinely used in our center to access occiput position when there is uncertainty following clinical examination, and this was a major detractor to recruitment of women for the trial, as several staff members felt that there was insufficient equipoise in these cases.…”
Section: Sirmentioning
confidence: 85%
“…Given the difficulty in recruiting patients for this trial, which was also reported by others, 4 we can only hope that further light will be shed on the subject from meta-analysis of the results.…”
Section: Sirmentioning
confidence: 87%
“…[25][26][27][28][29][30][31][32][33][34][35][36][37] On this basis, the use of ultrasound before vacuum or forceps is purported to provide a more precise placement of the instrument on the fetal head and subsequently to reduce the risk of failure of operative vaginal delivery and of related adverse events, including perinatal or maternal complications. 34,35,37,38 Although the studies conducted thus far were underpowered to demonstrate a significant difference in terms of clinical outcome, routine sonographic evaluation of fetal position and station before considering or performing a vaginal extraction is strongly endorsed by the recently published international guidelines on labor ultrasound. 39 In the management of other intrapartum complications or emergencies, such as postpartum hemorrhage or shoulder dystocia, despite the lack of specific recommendations and guidelines, the ancillary use of ultrasound, in addition to manual skills, is widely popular when refining and speeding up the diagnosis and treatment of the condition are not required.…”
Section: The Potential Usefulness Of Adding Ultrasound To Conventionamentioning
confidence: 99%
“…13 The role of intrapartum ultrasound as an ancillary method to perform operative vaginal deliveries has been the subject of several observational studies and of three randomized clinical trials. [14][15][16][17][18][19][20][21] However, the value of the combined transabdominal and transperineal approaches has yet to be evaluated in a randomized clinical trial. The aim of the present study was to compare transabdominal and transperineal ultrasound with routine clinical care before performing an instrumental vaginal delivery, regarding the incidence of adverse maternal and neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%